(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
The purpose of this paper is to present a methodology to identify the existence of threshold effects in the relationship between inflation and economic growth of Argentina, using non linear econometric procedures for estimation and inference. The empirical findings show that the threshold level of inflation above which inflation significantly slows growth is estimated at 12,9%. The level of inflation between 7,5% and 12,9% has no relevant effects on economic growth. The negative and statistically relevant relationship between inflation and growth is robust with respect to the econometric procedures considered, the exclusion of high-inflation observations, and the alternative specifications.